Today’s aspects of event management development - N. V. Yashkina (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2021)
Event management is a communication management or public relations tool which is being successfully used to obtain a lasting effect from a positively formed image of a business entity. An analysis made on available publications allowed classification of event management objects according to the level of accessibility and the degree of risk. It has been revealed that despite a significant number of publications, the issue of using a variety of event management tools remains insufficiently disclosed. It has been proven that corporate events require a planned strategic approach. Otherwise, there will be random measures and additional expenses with a zero result. To plan work in this direction, it is necessary to consider the corporate events as part of a general scheme of a PR-strategy. Before starting to design a corporate event, it is necessary to identify its purpose, objectives and a set of tools. Having obtained a clear understanding of what for, why and how the internal corporate event is to be organized, it is necessary to agree on a toolkit. It has been found that for the successful executing of an event, it is necessary to produce a standard plan which should include: a list of major events (exhibitions, presentations, round tables, press conferences, promo-actions, etc.); a list of main communication channels (TV, radio, newspapers, magazines, special directories, external advertising media, etc.); a list of materials to share through the communication channels (printed and text materials, souvenirs, information folders, etc.); a list of participants to the event (company speakers, company’s partners, competitors, VIPs, journalists, celebrities, etc.); a calendar plan; the budget. The prospect for further research is to design events focused on the creation of the company’s competitive advantages.